Proc. 28th Annual Conference of the International Group for Lean Construction (IGLC) 2020
DOI: 10.24928/2020/0027
|View full text |Cite
|
Sign up to set email alerts
|

Precast Concrete Building Construction Process Comparison

Abstract: Research shows that the precast construction process comprises waste and excessive lead times. The application of Lean Construction principles within the precast construction process varies from country to another due to different regional codes, market demands, informatics tools, fabrication and erection method, etc. This paper deploys value stream mapping (VSM) as a lean methodology to investigate and compare the process differences between a Canadian precast project and a Chinese precast project as basis fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…-Reduce delivery waiting times: AVs can deliver materials to the job site more frequently and more accurately, decreasing the wait time for materials to arrive, and cutting logistic costs (Xiaosheng & Hamzeh, 2020). AVs are able to calculate the most efficient route to the job site independently and can travel non-stop, which reduces travel time.…”
Section: Waste Reduction Through the Use Of Avsmentioning
confidence: 99%
“…-Reduce delivery waiting times: AVs can deliver materials to the job site more frequently and more accurately, decreasing the wait time for materials to arrive, and cutting logistic costs (Xiaosheng & Hamzeh, 2020). AVs are able to calculate the most efficient route to the job site independently and can travel non-stop, which reduces travel time.…”
Section: Waste Reduction Through the Use Of Avsmentioning
confidence: 99%
“…On the other hand, some studies have analyzed the benefits of using prefabricated components together with BIM and standardized processes. These studies have found increased performance in construction, such as reduced rework, reduced lead time, and better productivity (Xiaosheng & Hamzeh, 2020;Schimanski et al, 2021). Nevertheless, existing literature does not contain quantitative performance metrics.…”
Section: Introductionmentioning
confidence: 99%